Research Project: Poetry’s “Travel-Worthiness”: South America and Brazil Through the Eyes of English Language Poets - Annunciação, Viviane Carvalho da (ABEI Journal, 2017)
This research project aims at analyzing how physical and mentaltravels has helped poets to envision a new form of art and produce intercultural knowledge. Through a historical approach, I show the act of imagining a new land, outside the local culture, can be characterized as a transnational hybridization, articulating real and symbolic locales.